Impact of rheumatoid arthritis and biologic and targeted synthetic disease modifying antirheumatic agents on cancer risk and recurrence. Issue 3 (May 2021) - Singh, Namrata; Li, Christopher I.
Abstract : Purpose of review: Several new therapeutic drugs are now available for the management of rheumatoid arthritis (RA). Given that RA has been associated with an increased risk of certain cancers like lymphoma and lung cancer, concern remains about the safety of (newer) immunosuppressants used in RA management as it relates to the risk of cancer. Recent findings: Most meta-analyses of randomized clinical trials of tumor necrosis factor inhibitors (TNFi) have not observed an association between TNFi and risk of incident cancer. Studies of non-TNFi biologic disease modifying antirheumatic drugs (bDMARDs) and targeted synthetic DMARDs and cancer are also reassuring but limited and of short-term follow-up. Regarding the use of DMARDs in patients with RA and a prior malignancy, retrospective studies have shown that TNFi use is not associated with recurrence. Summary: There is a need for ongoing studies on the safety of non-TNFi bDMARDs and targeted synthetic disease modifying anti-rheumatic drugs and recurrent cancer. Further research is also needed to guide the patients, rheumatologists, and oncologists regarding the safest DMARDs to choose for patients with RA and a recent diagnosis of cancer.